Visceral leishmaniasis and Coombs’ positive hemolytic anemia: a rare association in an infant treated with liposomal amphotericin B - Dilber, Embiya; Erduran, Erol; Işık, Yasemin (The Turkish Journal of Pediatrics, 2002)
Visceral leishmaniasis is a worldwide, disseminated intracellular protozoal infection that usually manifests by fever, hepatosplenomegaly, anemia, thrombocytopenia, leukopenia and hypergammaglobulinemia. Although anemia is a usual finding, Coombs’ positive hemolytic anemia has rarely been reported in association with this disease. Pentavalent antimonials have been the preferred treatment for this disease for decades, but increasing numbers of treatment failure with antimony are being reported. Liposomal amphotericin B is a new drug which is highly efficacious in the treatment of visceral leishmaniasis and produces minimal toxicity. Here we report an infant with visceral leishmaniasis associated with Coombs’ positive hemolytic anemia who was successfully treated with liposomal amphotericin B.